2000
DOI: 10.1007/pl00004178
|View full text |Cite
|
Sign up to set email alerts
|

Axial and Total-Body Bone Densitometry Using a Narrow-Angle Fan-Beam

Abstract: We assessed a new dual-energy bone densitometer, the PRODIGY, that uses a narrow-angle fanbeam (4.58) oriented parallel to the longitudinal axis of the body (i.e., perpendicular to the usual orientation). High-resolution scans across the body can be stepped at 17 mm intervals. The energy-sensitive array detector uses cadmium zinc telluride, which allowed rapid photon counting. Spine and femur scans required 30 s, and totalbody scans required 4-5 min; the dose was only 3.7 mrem and 0.04 mrem respectively, or ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 24 publications
(45 reference statements)
0
34
0
1
Order By: Relevance
“…Two studies demonstrate that this technique is subject to negligible magnification effects (31,32); this latest advance may be particularly important for pediatric applications that rely on PA scans.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies demonstrate that this technique is subject to negligible magnification effects (31,32); this latest advance may be particularly important for pediatric applications that rely on PA scans.…”
Section: Discussionmentioning
confidence: 98%
“…However, as recent data from Leonard et al have shown that total body BMC, as assessed by DXA, correlates with pQCT-assessed measurements of bone strength when the data are adjusted for height [21], we also examined a subset of our cohort who were prepubertal, and adjusted their data for height and found that our observations persisted at the level of the lumbar spine. Concerns that the manufacturer's reference population may not accurately represent the normal range for our population are minimised by the recent publication of similar reference data using the same family of DXA scanners and the close concordance between the Lunar DPX and the Lunar Prodigy scanners [17,22].…”
Section: Discussionmentioning
confidence: 99%
“…The departure of our findings from those of Sopher et al (7) could be related to the use of DPX/DPX-L systems by the latter and a Prodigy system in the current study. Although Prodigy devices are calibrated to allow results to be obtained over a wide tissue thickness range (23), errors remain apparent at larger tissue thicknesses.…”
Section: Discussionmentioning
confidence: 99%